Media and occupational choice - Alexander Konon; Alexander Kritikos (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
We address the question of whether media influences occupational choices. To theoretically examine media effects, we construct a dynamic Bayesian occupational choice model with sequential decisions under ambiguity due to imperfect information. We show that sufficiently intensive positive media articles and reports about entrepreneurship increase the probability of self-employment and decrease the probability of wage work. To test our model, we use an instrumental variable approach to identify causal media effects using US micro data and a country-level macro panel with two different media variables. We find that an increase in positive media articles and reports about entrepreneurs generates effects on choice probabilities that are consistent with our model.
Keywords: D81; D83; J62; L26; 330; media; occupational choice; Bayesian learning; ambiguity aversion